Pengembangan Bahan Ajar Fikih Berbasis Mind Mapping dalam Pembelajaran Kitab Matnul Ghayah wat Taqrib di Madrasah Diniyah An-Nur II Bululawang - Muhammad Husni; Ari Abdi Widodo (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2026)
Fiqh learning in the chapter of prayer in Islamic schools often still focuses on memorizing the text and oral explanations, making it difficult for students to see the relationship between concepts such as conditions, pillars, sunnah, and invalidators of prayer. This study aims to describe the process of developing and implementing mind mapping-based fiqh teaching materials in learning the Matnul Ghayah wat Taqrib book and describe the responses of ustadz and students at Madrasah Diniyah An-Nur II Bululawang. The study used a descriptive qualitative approach with subjects of the teaching ustadz and 60 students in grade 3 of junior high school. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the teaching materials were developed by grouping prayer materials into main branches (obligatory conditions, valid conditions, pillars, sunnah, and invalidators of prayer) which were then visualized in the form of manual mind maps on the board and simple printed teaching materials. The integration of mind mapping makes the ustadz's explanations more focused, makes it easier for students to remember and differentiate legal categories, and increases their learning engagement. Despite time constraints and the large number of students, mind mapping is generally considered a feasible and effective alternative strategy for learning Islamic jurisprudence (fiqh) based on the yellow books in Islamic schools (madrasah diniyah).